2016
DOI: 10.1542/peds.2015-2970
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination and 30-Day Mortality Risk in Children, Adolescents, and Young Adults

Abstract: OBJECTIVE: This study evaluates the potential association of vaccination and death in the Vaccine Safety Datalink (VSD). METHODS:The study cohort included individuals ages 9 to 26 years with deaths between January 1, 2005, and December 31, 2011. We implemented a case-centered method to estimate a relative risk (RR) for death in days 0 to 30 after vaccination.Deaths due to external causes (accidents, homicides, and suicides) were excluded from the primary analysis. In a secondary analysis, we included all death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…These reported frequencies are similar to those observed with overall U.S. infant mortality data and among recipients of other recommended childhood vaccines ( 128 ). Two recent VSD studies do not suggest a causal relation or increased risk for death following vaccination of any type ( 129 , 130 ).…”
Section: Vaccines For Prevention Of Pertussis Tetanus and Diphtherimentioning
confidence: 93%
“…These reported frequencies are similar to those observed with overall U.S. infant mortality data and among recipients of other recommended childhood vaccines ( 128 ). Two recent VSD studies do not suggest a causal relation or increased risk for death following vaccination of any type ( 129 , 130 ).…”
Section: Vaccines For Prevention Of Pertussis Tetanus and Diphtherimentioning
confidence: 93%
“…That study found no association between vaccination and death within that 30-day window, for any vaccines evaluated. 110 No evidence of increased autoimmune and neurological conditions Numerous large studies have been conducted to evaluate the potential for increased risk of autoimmune disease after HPV vaccination. These include evaluations of nearly 350,000 HPV vaccine dose administrations, 111 270,000 girls, 112 568,000 boys, 113 nearly 1,000,000 adolescent females aged 10-17 years 114 and 3,100,000 adult females aged 18-44 years 115 .…”
Section: Vaccine Safety Data From Clinical Trialsmentioning
confidence: 99%
“…Influenza is a common disease that causes annual epidemics, leading to medical, social and economic problems [23,24]. Together with the elderly population, children under 5 years of age, even in the absence of underlying chronic diseases, have the highest risk of severe disease leading to hospitalization and, although rarely, to death [25].…”
Section: Influenza Vaccinationmentioning
confidence: 99%